Narcoculture and Crisis of Identity in «El amante de Janis Joplin», of Élmer Mendoza (Castilla. Estudios de Literatura, 2017)
The present study seeks to interpret the discursive formations inscribed in the novel by Élmer Mendoza, El amante de Janis Joplin (2001), as a transcript of the collective identity around the phenomenon of narcoculture. For this, we will use the Foucault´s reflection on the aspects involved in the process of gestation of discourse as a heuristic axis on which the knowledge of the social imaginary inscribed in the text.
Keywords: Élmer Mendoza; narcoliteratura; Michel Foucault; México; identity; El amante de Janis Joplin